2022
DOI: 10.3390/ijerph192113729
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Polish Doctors towards Brain Death

Abstract: Brain death has been one of the most controversial issues in the medical and bioethical debate globally for more than fifty years. There is no unanimous acceptance of the understanding of brain death, and a single set of neurological criteria for the determination of human death that is accepted worldwide has yet to be established. Physicians from different specialisations understand brain death differently. Therefore, research is needed to understand and typologically classify their points of views as regards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…68,69 Finally, Zheng et al performed a scoping review of 75 papers published from 2003 to 2020 on trainee and health care professionals' knowledge and attitudes about the concept of BD/DNC. [70][71][72][73] They demonstrated that BD/DNC is widely accepted, but it remains controversial and there are varying views on its conceptual basis.…”
Section: Background and Overview Of New Publicationsmentioning
confidence: 99%
“…68,69 Finally, Zheng et al performed a scoping review of 75 papers published from 2003 to 2020 on trainee and health care professionals' knowledge and attitudes about the concept of BD/DNC. [70][71][72][73] They demonstrated that BD/DNC is widely accepted, but it remains controversial and there are varying views on its conceptual basis.…”
Section: Background and Overview Of New Publicationsmentioning
confidence: 99%